2012
DOI: 10.1024/0300-9831/a000128
|View full text |Cite
|
Sign up to set email alerts
|

Discovery-Based Nutritional Systems Biology: Developing N-of-1 Nutrigenomic Research

Abstract: Biological and biomedical research, like many established human activities, is based on conventions and practices that become standardized over time. Many of these conventions are decades old and do not account for the great advances in knowledge resulting from modern research. Some of the main practices of biomedical research are discussed herein, in an attempt to initiate a dialogue in the nutrition community about new concepts for personalized nutrition and health. The Design of ExperimentsThe design of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The bioavailability and bioactivity of micronutrients and bioactives differ widely according to chemical structure. Intake from dietary supplements and foods differ in content, matrices, and dose Gaine et al (2013) The micronutrient and bioactive content of plant foods is influenced by numerous plant-related factors (e.g., sun, ripeness, storage, preparation, processing), making accurate assessment of their intake difficult Gaine et al (2013) Errors in intake measurement: accuracy of food composition databases and reliability of FFQs, and intake amounts do not always equate to bioavailable doses Gaine et al (2013) The health benefits of micronutrients and bioactives in the current literature are often based on surrogate biomarkers of effect rather than actual health outcomes (endpoints), such as disease incidence or mortality Gaine et al (2013) Classical case/control designs of human clinical/nutritional intervention studies should be complemented by crossover, longitudinal studies, in which every subject is its own case and control Kaput and Morine (2012) Homeostasis varies among individuals. Challenging homeostasis may identify individual health trajectories van Ommen et al (2009) The funding required in undertaking a formal federal review of micronutrient and bioactive intake has not been viewed as a priority Gaine et al (2013) …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The bioavailability and bioactivity of micronutrients and bioactives differ widely according to chemical structure. Intake from dietary supplements and foods differ in content, matrices, and dose Gaine et al (2013) The micronutrient and bioactive content of plant foods is influenced by numerous plant-related factors (e.g., sun, ripeness, storage, preparation, processing), making accurate assessment of their intake difficult Gaine et al (2013) Errors in intake measurement: accuracy of food composition databases and reliability of FFQs, and intake amounts do not always equate to bioavailable doses Gaine et al (2013) The health benefits of micronutrients and bioactives in the current literature are often based on surrogate biomarkers of effect rather than actual health outcomes (endpoints), such as disease incidence or mortality Gaine et al (2013) Classical case/control designs of human clinical/nutritional intervention studies should be complemented by crossover, longitudinal studies, in which every subject is its own case and control Kaput and Morine (2012) Homeostasis varies among individuals. Challenging homeostasis may identify individual health trajectories van Ommen et al (2009) The funding required in undertaking a formal federal review of micronutrient and bioactive intake has not been viewed as a priority Gaine et al (2013) …”
Section: Discussionmentioning
confidence: 99%
“…The first is the insistence on randomization for clinical studies, and the second is the reductionist's approach used to study complex systems. While randomization was essential for pregenomic era research (Fisher 1971), the ability to characterize individuals at the genetic, proteomic, and metabolomic level demonstrated that this statistical approach-also by definition-masks inter-individual variation in response not only to nutrients but also to drugs (Guyatt et al 1990;Lillie et al 2012;Kaput and Morine 2012). Similarly, the one-gene-one-polypeptide concept best exemplified by Beadle and Tatum's 1941 analysis of auxotrophy in Neurospora sp.…”
Section: Genetic and Epigenetic Variability: Molecular Phenotypingmentioning
confidence: 99%
See 3 more Smart Citations